The poetics of land & identity among British Columbia Indigenous peo ples - Elsey, Christine J., 1953- (Halifax, N.S. : Fernwood Pub., 2013)
"The Poetics of Land and Identity is about the meaning of land for t he many diverse First Nations within British Columbia. The work offers a study of the folklore and symbolic traditions within many Aboriginal regions and illustrates how these traditions emphasize the importance o f orality and poetics as the defining factor in the value of land. Chri stine J. Elsey offers a deft, scholarly discussion of these "storyscape s," providing us with a point of access for understanding First Nations ' perspectives on the world and their land. She provides an important a lternative to the monetary, exploitative, resource-driven view of natur e and land ownership and highlights the conflicts between the colonial, Western perspective of nature and the holistic view of First Nations p eople."--Publisher's website.
Introduction -- First Nations Identity Through a History of Struggle -- The Poetics of Self and Land; A Phenomenological Explanation -- Poe tics and Stories Among the Coastal First Nations -- The Poiesis of Land in Interior "Storyscapes" -- The Poiesis of Enfoldment Within the Stei n Valley "Storyscape" -- Conclusion -- Glossary -- Appendices -- Select ed Bibliography -- Index.
Includes bibliographical references (p. 127-135) and index.
Keywords: Indigenous peoples -- British Columbia -- Ethnic identity; Indigenous peoples -- Land tenure -- British Columbia; Folklore -- British Columbia; Indigenous peoples -- British Columbia; Native peoples -- Land tenure -- British Columbia; Native peoples -- British Columbia -- Ethnic identity; Native peoples -- British Columbia -- Folklore; British Columbia -- Social life and customs